QR Code as a Supplement of the Traditional Monograph. Advantages and Consequences - Mateusz Sikora (Toruńskie Studia Bibliologiczne, 2017)
The article describes the possibility of using QR codes in traditional scientific monographs. By using this kind of tools authors have an opportunity to disseminate results of their work in a pose-text way. That way of publishing is attractive to authors – they gain additional opportunity to present their theses, as well as for readers, for whom such a message may be more attractive. The use of modern technologies in the process of publishing scientific monographs may also raise concerns. The consequences resulting from the tabloidization of the science sphere can be dangerous for the authority of the scientific community. The article presents an example of a monograph where authors decided to use QR codes as a complement to the traditional monograph. The publication included results of qualitative research conducted by anthropologists in Lithuania.